2020
DOI: 10.1039/c9cc09563b
|View full text |Cite
|
Sign up to set email alerts
|

Modified cation-exchange membrane for phosphate recovery in an electrochemically assisted adsorption–desorption process

Abstract: A novel ion separation methodology using a cation-exchange membrane modified with iron oxide nanoparticles (Fe3O4 NPs) coated with polyhexamethylene guanidine (PHMG) is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The use of IEMs coated with layers that selectively sorb phosphates is another promising direction for increasing the current efficiency in the recovery of phosphates. For example, Petrov et al [ 244 ] propose to use CEM modified with high surface area adsorbent with iron oxide nanoparticles (Fe 3 O 4 NPs) coated with polyhexamethylene guanidine. This polyelectrolyte enters into a selective interaction with phosphate [ 245 ].…”
Section: Innovations In Nutrient Recovery Processes With Ion-exchange...mentioning
confidence: 99%
“…The use of IEMs coated with layers that selectively sorb phosphates is another promising direction for increasing the current efficiency in the recovery of phosphates. For example, Petrov et al [ 244 ] propose to use CEM modified with high surface area adsorbent with iron oxide nanoparticles (Fe 3 O 4 NPs) coated with polyhexamethylene guanidine. This polyelectrolyte enters into a selective interaction with phosphate [ 245 ].…”
Section: Innovations In Nutrient Recovery Processes With Ion-exchange...mentioning
confidence: 99%
“…The phenomena of the rejection and adsorption on the surfaces and interfaces of the self-assembled multilayers driven by electrostatic interaction are closely related to their applications such as ion adsorption, separation, and desalination. For example, Armstrong et al reported that a 30 nm-sized pore structure modified by poly­(styrene sulfonate)/protonated poly­(allylamine) (PAH) multilayers showed Br – /SO 4 2– selectivity of 3.4 with a SO 4 2– rejection rate of 85%. This is due to the selective electrostatic rejection of the negatively charged pore and the divalent anions.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorptive membranes are an emerging class of materials with improved separation performance compared to conventional membranes (4,(10)(11)(12)(13)(14). However, limited tunability, capacities, and selectivities remain major challenges in their development (4).…”
mentioning
confidence: 99%
“…Adsorptive membranes are an emerging class of materials that have been shown to exhibit improved performance in numerous separations when compared with conventional membranes, including for water purification (4,(9)(10)(11)(12)(13). However, improvements are needed in the capacities, selectivities, and regenerabilities achievable with these materials to enable their wide-scale use, which is also currently hindered by the limited structural and chemical tunability of most adsorptive membranes (4).…”
mentioning
confidence: 99%